Padrões fitogeográficos da região central do domínio atlântico brasileiro - Felipe Zamborlini Saiter (2015)
Restinga forests are one of the most endangered and neglected ecosystems of the South America and their pythogeographic patterns are poorly known. Here, we submitted climatic and occurrence data of tree species from Restinga sites in the central part of the Atlantic forest tonumerical analyses in order to determine the role of climate and geographical location of sites in a latitudinal floristic gradient, and to discuss the implications of such patterns for conservation. We confirmed the existence of such a gradient, one that was strongly related to climaticseasonality, and especially to temperature seasonality. Within this gradient, we noticed a stronger variation in composition in a region known for its transitional climate, from seasonal to nonseasonal.The shifts in climatic seasonality can be explained by a set of atmospheric and oceanographic phenomena and by geographical relief inland. Geographical location influences species composition because spatial proximity means similarity in climatic conditions, althoughdispersal difficulties can also limit the distribution of some species. Within the study region, we recognize the Regência-Prado stretch as the most relevant area for conservation of Restingas, because of the paucity of reserves and the high floristic variation within a relatively shortdistance along the coast.